An elastoplastic damage ice material model based on modified Tsai-Wu yield criterion: Experiment, theory and numerical application - Li, Junxing; Yang, Jiajia; Liu, Qi; Xu, Jun; Zhang, Wenyuan; Yang, Qiyong (Construction & building materials, 2024)
Ice, as a novel green and sustainable building material, has attracted more and more attention in building engineering. Appropriate ice material models are crucial for the performance analysis of the increasing ice structures. There is still challenging in modelling ice responses due to the complexity of ice. This study aims to present a nonlinear elastoplastic damage model for ice material. First, a triaxial compression test of artificial ice is conducted. Based on the test results, the modified Tsai-Wu failure criterion with better performance in the tensile zone and physical meaning for hydraulic strength is established. Then, combining plasticity theory with damage mechanics, an elastoplastic damage constitutive law considering the difference between tensile and compressive properties is proposed. The piecewise damage model and the Weibull exponential damage model are employed for compression and tension damage, respectively. Moreover, the numerical iterative algorithm is developed and a user-defined material subroutine (UMAT) is embedded in the finite element software ABAQUS to simulate the mechanical properties of ice. Furthermore, the constitutive model is verified by comparing the FEM results with the results of uniaxial compression, triaxial compression, and three-point bending tests. The results show that the constitutive model can well describe the stress-strain nonlinear behavior and capture the basic failure mode of ice materials. Finally, considering temperature affecting on the failure surface, a temperature dependent ice material model is developed. The current study would help in the design, operation and maintenance of ice structures. •A modified Tsai-Wu failure criterion is provided and compared by triaxial tests.•The yield surface evolution and damage evolution are considered.•A fiber damage model based on Weibull theory is proposed for ice under tension.•Theory and implementation of the elastoplastic damage model for ice are presented.•Temperature-dependent elastoplastic damage constitutive model is developed.